Study on the stability of foamed gel and its structural evolution characteristics - Qing, Guo; Wanxing, Ren; Wei, Lu (Combustion science and technology, 2023)
Foamed gel is an efficient material for coal spontaneous combustion prevention and control, which effectively combines the fire prevention and extinguishing properties of foam and gel. In this paper, the formation principle, structural evolution, stability, and fluidity of foamed gel are elaborated. Foamed gel is mainly formed by foaming agent, cross-linking agent and water through physical foaming and gelling reaction, and its formation process is divided into two stages: the first stage is physical foaming and forming foam; the second stage is adding cross-linking agent to foam and generating foamed gel through gelling reaction. The first stage of foamed gel mainly reflects the fluidity and stacking of foam, and in the second stage, with the increase of gel amount, foamed gel reflects the temperature resistance of gel. The basic structure of the foamed gel is the same as that of the water-based foam, and the gel particles constitute the basic skeleton of the foamed gel, which slows down the gravitational drainage and foam disproportionation rate. The evolution process of foamed gel structure includes liquid film rupture, gel formation and skeleton collapse, which eventually forms a gel layer to fill the residual coal fissure. The flow of foamed gel in the mining area is subject to the combined effect of grouting pressure, gravity and resistance, and the lateral flow velocity is larger than the longitudinal flow velocity, and the contour line of its diffusion front peak is ellipsoidal.